Hepatolenticular degeneration: analysis of neurological manifestations under treatment in 76 patients - Egberto R. Barbosa; Milberto Scaff; Horácio M. Canelas (Arquivos de Neuro-Psiquiatria)
A series of 76 patients with hepatolenticular degeneration (HLD) followed up at the Hospital of the University of São Paulo Medical School between 1963 and 1988 have been studied focusing the evolution under treatment of neurological features. The assessment of neurological symptoms included 12. specific items, and it was made by a scoring system ranging from 0 to 3 (absent, mild, moderate and severe). Global score varied between 0 to 36. A functional disability scale (0, normal; 1, mild; 2, moderate; 3, severe) was also adopted. All patients received D-penicillamine but three of them developed serious renal toxic side-effects, and this drug was replaced by zinc (sulphate or acetate). Fifty-nine patients (77.6%) improved, 8 (10.6%) remained unchanged, and 9 (11.8%) got worse. The main features related to bad results were poor compliance, predominance of dystonic symptoms, and short time treatment (death due hepatic complications). Eight patients (10.5%) developed transient worsening of neurological symptoms during the first weeks of treatment. Three patients who have D-penicillamine replaced by zinc salts presented satisfactory evolution. From them, only one had neurological symptoms. Death due to infectious complications related to severe motor disability occurred in three patients, representing only 10.7% of fatal evolution.